2020
DOI: 10.1155/2020/8848225
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Urinary Amino Acid Profile Characterizes People with Kidney Stones

Abstract: Background. Urolithiasis is the process of stone formation in the urinary tract. Its etiology is only partly known, and efficient therapeutic approaches are currently lacking. Metabolomics is increasingly used in biomarkers discovery for its ability to identify mediators of relevant (patho)physiological processes. Amino acids may be involved in kidney stone formation. The aim of the present study was to investigate the presence of an amino acid signature in stone former urine through a targeted metabolomic app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The sample matrices reported in this study suggest that there is a growing interest in minimally invasive sample types. The majority (66.67%) of the TRP urine papers have been published since 2015, 28 , 53 , 57 , 63 , 90 , 96 , 110 , 124 , 134 , 136 while all included TRP saliva studies were published within this timeframe. 38 , 71 Saliva metabolomics is an emerging field of research due to the diversity of metabolites present and the relative ease in sampling including decentralised approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The sample matrices reported in this study suggest that there is a growing interest in minimally invasive sample types. The majority (66.67%) of the TRP urine papers have been published since 2015, 28 , 53 , 57 , 63 , 90 , 96 , 110 , 124 , 134 , 136 while all included TRP saliva studies were published within this timeframe. 38 , 71 Saliva metabolomics is an emerging field of research due to the diversity of metabolites present and the relative ease in sampling including decentralised approaches.…”
Section: Discussionmentioning
confidence: 99%
“…New urinary biomarkers have been identified [ 44 ] and metabolomic studies are promising. For instance, a study identified a urinary amino acid profile specific to kidney stone formers [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as the search equations did not include metabolomics, we conducted a focus search in PubMed with the terms “metabolomics” and “kidney stones” in January 2021. This search gave 16 results, two publications were selected and added to the review [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, there has been a rapid increase in the use of metabolomics for the treatment of RC due to the development and popularization of metabolomics technology. Some researchers have already conducted metabolic profiling on the urine of RC patients using 1H NMR [ 8 , 9 ] and targeted amino acid methods [ 10 ]. Reports on untargeted metabolomics [ 11 ], lipid metabolism [ 12 ], and bile acid metabolism [ 13 ] in animal models of RC are also on the rise.…”
Section: Introductionmentioning
confidence: 99%